2018
DOI: 10.4103/ijpc.ijpc_34_18
|View full text |Cite
|
Sign up to set email alerts
|

The development of the community-based palliative care model in a district health system, Phitsanulok Province, Thailand

Abstract: Context:Palliative care (PC) refers to a set of basic health services in Thailand and is in the early stage of implementation.Aim:The aim of this study is to develop a community-based PC model in a district health system (DHS) based on the form of action and evaluation.Methods:A three-step action research: look, think, and act was designed with mixed methods of data collection.Results:A key finding was the confusion on the terminology of the PC, challenge of the referral system of PC patients in DHS, medical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…I am concerned about the drug abuse; therefore, this DHS does not prescribe Morphine to be used in the community/at home. We need to set a guideline first.” [PHAR1 (p343)] 40…”
Section: Prescribingmentioning
confidence: 99%
See 1 more Smart Citation
“…I am concerned about the drug abuse; therefore, this DHS does not prescribe Morphine to be used in the community/at home. We need to set a guideline first.” [PHAR1 (p343)] 40…”
Section: Prescribingmentioning
confidence: 99%
“…We need to set a guideline first." [PHAR1 (p343)] 40 Clinical guidelines for pain relief are reported within included studies as enablers of access to opioids. In the Philippines, a survey of clinicians found that 72% were aware of the WHO Ladder for Pain Control.…”
Section: Prescribingmentioning
confidence: 99%
“…Palliative care is commonly situated within some type of health care institution—hospitals, clinics, nursing homes, outpatient, and in-home settings. Community-based palliative care delivery models can improve quality of care and positively affect caregivers and family lived experiences (Bhavsar et al, 2017; Kitreerawutiwong et al, 2018). Community-based palliative care models are designed to support patients, families, and caregivers across the continuum of advanced illness rather than focusing on the period just before death (Kamal et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There have been continuing efforts to develop a protocol for palliative care provision in Thailand's context. In fact, many guidelines and quality of care measuring tools are available for wider use [9][10][11]; nevertheless, most Thai hospitals report following the guidelines developed in each facility [12]. In addition to the nationwide implementation of palliative care performance indicators related to some care process (e.g., opioid drug provision; advance care planning; home visit) [13][14], there is no clear protocol for the provision of facility-based palliative care in the country [12].…”
Section: Introductionmentioning
confidence: 99%